If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -1) = 3x + 12 Reorder the terms: x(-1 + x) = 3x + 12 (-1 * x + x * x) = 3x + 12 (-1x + x2) = 3x + 12 Reorder the terms: -1x + x2 = 12 + 3x Solving -1x + x2 = 12 + 3x Solving for variable 'x'. Reorder the terms: -12 + -1x + -3x + x2 = 12 + 3x + -12 + -3x Combine like terms: -1x + -3x = -4x -12 + -4x + x2 = 12 + 3x + -12 + -3x Reorder the terms: -12 + -4x + x2 = 12 + -12 + 3x + -3x Combine like terms: 12 + -12 = 0 -12 + -4x + x2 = 0 + 3x + -3x -12 + -4x + x2 = 3x + -3x Combine like terms: 3x + -3x = 0 -12 + -4x + x2 = 0 Factor a trinomial. (-2 + -1x)(6 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {-2, 6}
| 16x^2-56x+49=28 | | 5(y-5)=7y-25 | | -8x+3y=12 | | 0.4x-0.5(3)=2.1 | | y-34=-213 | | -2(x+4)-10(25-x+4)=5-3x-4(x+1) | | 3-(2w+5)= | | 2t3+4t2-30t | | y=5mx | | -7(y-1)=21 | | 0.51+0.24t=2.28t-0.85 | | 1/7(3y+4)=5+1/5(y+3) | | 3.4x+50.9=21.7-11.2x | | 3lnx=6-2x | | 3lnx=6-2 | | 2/3x=1/2x+3 | | 3.4x+50.9+21.7-11.2x | | 6x+5+7x+3x=12x+4 | | 23(16-x=5(2x+1) | | y-13=22 | | xy=tz | | -b/10=-3 | | 2x^2+2y^2-12x+8y+18=0 | | y*2=116-80 | | y*2=116-48 | | y*2=116-44 | | 5+8(x+2)=6(1+x)-1 | | y*2=116-40 | | 2(5-8)+9= | | 11=-n/7 | | 7/x=17/9 | | y*2=116-28 |